Psychological research of the formation of professional identity in psychology students - Sadykova N. М.; Zhubanazarova, N. S.; Baimoldina, L. O.; Akhtaeva, N. S.; Omirbek, G. A. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2019)
In article are considered questions of formation of psychologists in the conditions of educational space of the University, where one of the main criteria of professional competence of future psychologists is the level of development of professional selfconsciousness and identity. A multidimensional approach to the analysis of professional identity is one of the possible directions of the formation and correction of the professional identity of the future specialists. A person becomes “completely human” when he realizes his identity. Identity is the mental component of selfawareness, which is formed and exists in the human world. We know who we are, we are aware of our identity in the world of people, professions, nations, etc. In this regard, the experience of identity and in the professional sphere of human life is of particular importance. In the theory and practice of professional development, the need for a new understanding of the nature and meaning of work of specific professionals, the specifics of professional selfdetermination is increasingly felt, and the problems associated with the development of professional identity are coming to the fore. Key words: identity, selfconsciousness, psychologists, institution of higher education, formation, training.